Vanity fair a novel without a hero - Thackeray, William Makepeace 1811-1863 (Riverside editions, 1963)
Vanity Fair is a story of two heroines---one humble, the other a scheming social climber---who meet in boarding school and embark on markedly different lives. Amid the swirl of London's posh ballrooms and affairs of love and war, their fortunes rise and fall. Through it all, Thackeray lampoons the shallow values of his society, reserving the most pointed barbs for the upper crust. What results is a prescient look at the dogged pursuit of wealth and status---and the need for humility.